Analisis Strategi Jual Beli Topi Online Melalui Facebook dengan Sistem Lelang Ditinjau Dari Perspektif Islam - Fadhurrozi Fadhurrozi; Abdur Rohman (LP2M IAI Miftahul Ulum Pamekasan, 2023)
The presence of social media brings fresh air to business actors to always develop their business. By utilizing the social media platform, business actors can conduct mu'amalah transactions with anyone and at any time without being limited by space and time. Facebook social media is social media that is used as a forum by its users to buy and sell online with an auction This study uses a descriptive qualitative approach that focuses on the actual description of the condition of one of the cases. Descriptive qualitative research aims to describe existing phenomena, both scientifically and man-made, in the form of changes in activity, characteristics, changes in the relationship of similarities and differences between one another. The results of this study indicate that buying and selling online with an auction system on Facebook can be used as a reference as a strategy for marketing products in an online buying and selling system. The strategy of buying and selling online with an auction system from an Islamic perspective makes economic development for business actors buying and selling online with an auction system.